Reimagining Marine Energy: Tidal Rhythms, Language and Community in ebban an’ flowan - Monika Szuba (Angles)
This article proposes a discussion of Alec Finlay, Laura Watts and Alistair Peebles’s ebban an’ flowan (2015), employing the concept of paratexts developed by Gérard Genette. It looks at the ways in which cultural production and renewable energy may cross-pollinate, taking into account language, experiment, tradition and local community. Focusing on the textual thresholds or fringes, the article analyses the cross-medial aspects of ebban an’ flowan, which aim to re-empower the regional culture of the Orkney Islands characterised not only by high complexity, but also technological innovation. Engaging with energy humanities, the essay seeks to demonstrate a potential of a literary work to offer a vision for integrating tidal energy into a sustainable future for maritime communities.